EFEKTIFITAS TEKNIK MODELING SIMBOLIS UNTUK MENINGKATKAN MOTIVASI BERPRESTASI SISWA SMP NEGERI 2 MINASATENE - Pratiwi, Ardila (STKIP Andi Matappa, 2017)
The purpose of this research is (1) To determine student achievement motivation level overview of SMP Negeri 2 Minasatene, (2) To determine the effectiveness of modeling symbolic techniques in improving student achievement motivation SMP Negeri 2 Minasatene. This research is a quantitative research. kind of experiment in the form of One-group pretest-posttest design. The population is students of SMP Negeri 2 Minasatene and the sample size is 33 students. The technique of collecting using questionnaires, observation and documentation. The analysis using descriptive and inferential statistical t-test. The results showed that (1) The level of student achievement motivation SMP Negeri 2 Minasatene before being given a modeling symbolic techniques that are in the mean score of 99.18 are included in the high category and after being given the modeling symbolic techniques increases with the mean score of 105.88 which included the category of very high. This improvement can also be seen from the number of students who have a very high achievement motivation at the time before the application of symbolic modeling technique is 15 people, or approximately 45.5%, and after being given the modeling symbolic techniques increased to 24 people, or approximately 72.7%. (2) The value of 16.089 t count greater than 2.037 to 0.05 and received ttable research hypothesis which states